In silico mining of microsatellites in coding sequences of the date palm (Arecaceae) genome, characterization, and transferability1. (7th January 2014) - Aberlenc‐Bertossi, Frédérique; Castillo, Karina; Tranchant‐Dubreuil, Christine; Chérif, Emira; Ballardini, Marco; Abdoulkader, Sabira; Gros‐Balthazard, Muriel; Chabrillange, Nathalie; Santoni, Sylvain; Mercuri, Antonio; Pintaud, Jean‐Christophe
Abstract : Premise of the study: To complement existing sets of primarily dinucleotide microsatellite loci from noncoding sequences of date palm, we developed primers for tri‐ and hexanucleotide microsatellite loci identified within genes. Due to their conserved genomic locations, the primers should be useful in other palm taxa, and their utility was tested in seven other Phoenix species and in Chamaerops, Livistona, and Hyphaene . Methods and Results: Tandem repeat motifs of 3–6 bp were searched using a simple sequence repeat (SSR)–pipeline package in coding portions of the date palm draft genome sequence. Fifteen loci produced highly consistent amplification, intraspecific polymorphisms, and stepwise mutation patterns. Conclusions: These microsatellite loci showed sufficient levels of variability and transferability to make them useful for population genetic, selection signature, and interspecific gene flow studies in Phoenix and other Coryphoideae genera.